Room temperature tunable multicolor phosphorescent polymers for humidity detection and information encryption. Issue 13 (14th March 2022) - Gao, Yulei; Di, Xiang; Wang, Fenfen; Sun, Pingchuan
Abstract : A polymer with tunable multicolor was prepared via copolymerizing a phosphor with concentration dependent luminescence and acrylamide based on chemical crosslinking and hydrogen bonding interactions for humidity detection and information encryption. Abstract : Amorphous polymer-based room temperature phosphorescence (RTP) materials exhibiting tunable emission colors have received tremendous attention and are extremely challenging to prepare. Herein, polyacrylamide-based RTP materials with tunable multicolor emission were prepared via copolymerizing phosphor with concentration dependent luminescence colors and acrylamide with different molar ratios. The hydrogen bonding interactions and chemically crosslinked structures in these polymers effectively restrict the mobility of phosphors and activate efficient RTP emission. The molar ratio of phosphor and acrylamide has a significant influence on the photophysical properties of these polymers, which can be used to fabricate multicolor materials. In addition, the RTP intensity decreases with increasing humidity due to the disassociation of hydrogen bonding by adsorption of water, manifesting as a humidity sensor. Benefiting from the distinguishable RTP lifetimes and the responsiveness to humidity, triple encoding for information encryption is successfully realized.